Word order in Hungarian : the syntax of Ā-positions - Puskás, Genoveva (Linguistik aktuell, 2000)
Hungarian word-order is characterized by large scale preposing of constituents to sentence-initial positions. This study examines systematically the elements which occur in the left periphery. Focal, wh- and negative operators which have scope over the whole sentence must appear in the left periphery overtly; topicalized elements precede the scope operators and appear in an organized system as well. The author proposes that the structure of the Hungarian sentence comprises a rich set of left-peripheral functional projections, organized into sub-systems, like the Scope field and the Topic field.